(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2025)
Rare-earth hexaborides (RB6) are attractive materials for photonic, electronic, and energy applications owing to their unique crystal and electronic structures. Conventional synthesis methods, however, are limited by very high temperatures, long reaction times, and the use of complex precursors. In this work, we report a rapid and energy-efficient microwave-assisted synthesis (MS) method for the preparation of RB6 powders. Using simple precursors (lanthanide oxides and elemental boron), hexaborides of La and Pr were successfully obtained within only 10 min, despite the thermodynamic constraints of the R2O3/B → RB6 reaction systems. Structural and morphological characterizations (XRD, XPS, SEM/EDS) confirmed the formation of highly crystalline cubic phases with uniform particle sizes in the 1–5 μm range. For heavier lanthanides (Gd, Ho, Er), mixed boride and borate phases were observed instead of pure hexaborides. These results demonstrate the potential of MS for overcoming thermodynamic barriers and enabling fast, energy-efficient synthesis of selected lanthanide hexaborides.